Can chlorination of ballast water reduce biological invasions?. Issue 2 (17th November 2019) - Lin, Yaping; Zhan, Aibin; Hernandez, Marco R.; Paolucci, Esteban; MacIsaac, Hugh J.; Briski, Elizabeta
Abstract: Ballast water has been identified as a leading vector for introduction of non‐indigenous species. Recently, the International Maritime Organization implemented management standards—D‐2—where all large, commercial ships trading internationally are required to adopt an approved treatment system using technologies such as ultraviolet radiation or chlorination. However, current management regulations are based only on the total abundance of viable taxa transported (i.e. total propagule pressure), largely ignoring species richness (i.e. colonization pressure). To determine the efficacy of chlorine treatment in reducing invasion risks and changes in transported biological communities inside ballast tanks, we used DNA metabarcoding‐based approaches to estimate colonization pressure (here, the number of species/operational taxonomic units [OTUs] introduced) and relative propagule pressure (relative abundance of each species/OTU) of zooplankton communities in control and chlorine treated tanks during four transatlantic voyages. Our study demonstrated that transport itself did not significantly reduce colonization pressure of zooplankton species, nor did chlorine treatment. Chlorine treatment altered community structure by reducing relative propagule pressure of some taxa such as Mollusca and Rotifera, while increasing relative propagule pressure of some Oligohymenophorea and Copepoda species. Synthesis and applications. Chlorine treatment may not reduce invasion risks as much as previously thought. Reduction in total propagule pressure does not mean reduction in abundance of all species equally. While some taxa might experience drastically reduced abundance, others might not change at all or increase due to hatching from dormant stages initiated by chlorine exposure. Therefore, management strategies should consider changes in total propagule pressure and colonization pressure when forecasting risk of new invasions. We therefore recommend adopting new approaches, such as DNA metabarcoding‐based methods, to assess the whole biodiversity discharged from ballast water. As species responses to chlorine treatment are variable and affected by concentration, we also recommend a combination of different technologies to reduce introduction risks of aquatic organisms. Abstract : Current ballast water management regulations are based only on the total propagule pressure, largely ignoring colonization pressure. While "selection model" (Briski et al., 2018) suggests that reduction in total propagule pressure during transport does not mean reduction in abundance of all species equally, our study demonstrated that chlorine treatment altered community structure by reducing relative propagule pressure of some taxa but increasing relative propagule pressure of other taxa. Therefore, management strategies should consider changes in total propagule pressure and colonization pressure when forecasting risks of new invasions. Foriegn Language Abstract 中文摘要: 压舱水被认为是全球范围内外来生物传播的重要载体。近期, 《国际船舶压载水及沉积物控制与管理公约》中的D‐2标准正式生效, 这意味着所有进行国际贸易的商业船舶均需要安装基于紫外和氯处理等一系列处理技术的船载压舱水处理系统, 以实现压舱水的达标排放。然而, 现有的管理条例仅仅基于压舱水所传播的存活生物的总丰度（即总繁殖体压力 total propagule pressure）, 而极大忽略了物种丰度（即定植压力 colonization pressure）. 为了评估氯处理技术在减少入侵生物风险中的效率及其对压舱水中浮游动物群落结构及多样性变化的影响, 我们运用DNA宏条形码技术, 比较了四条跨大西洋航线中的空白对照和氯处理压舱水间的浮游动物群落的定植压力【即传播的物种数/操作分类单元（OTUs）数】和相对繁殖体压力（物种/OTUs的相对丰度)。 我们的结果表明, 压舱水传播过程本身（即未经过处理的对照）和氯处理均未能显著减少浮游动物的定植压力。氯处理能有效改变浮游动物群落结构, 一些类群的相对繁殖体压力减少, 例如软体动物和轮虫；而另一些类群的相对繁殖体压力增加, 例如寡膜纲和桡足纲的部分物种。 总结与应用: 氯处理在降低入侵风险方面可能低于预期。总繁殖体压力的降低并不代表所有物种丰度也随之相同程度地降低。一些类群的丰度可能急剧降低, 而另一些类群的丰度则并不改变, 甚至由于氯暴露引发的休眠体孵化而导致部分类群的相对丰度增加。因此, 在预测新的入侵风险时, 管理策略应综合考虑总繁殖体压力和定植压力。因此, 我们也建议采纳新的技术方法来综合评估压舱水中的生物多样性, 例如 DNA 宏条形码技术等。鉴于不同生物对氯处理的响应不同, 我们建议采取多种压舱水处理技术相结合的方法以减少外来水生生物的引入与传播。